ALGORITMA ECLAT SEBAGAI ALAT BANTU PENGELOLAAN PERSEDIAAN BARANG - Fatkhul Huda, Alfian; Jananto, Arief (Information Technology and Telematics, 2018)
Abstract - Tokokita is a mini market that sells groceries, stationery and others. Stores We have used barcodes for the sale of all items that exist. But TokoKita often finds obstacles in the inventory of goods because they do not have guidelines for benchmarking in the preparation of the next inventory. TokoKita transaction data from November 2016 to October 2017 is used to explore information on the relationship of an item. The research method used in this study is CRISP-DM which consists of business understanding, data understanding, data preparation, modeling, evaluation, and deployment.